If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 11n + -5 = 9n + 12 + -7n Reorder the terms: 8 + -5 + 11n = 9n + 12 + -7n Combine like terms: 8 + -5 = 3 3 + 11n = 9n + 12 + -7n Reorder the terms: 3 + 11n = 12 + 9n + -7n Combine like terms: 9n + -7n = 2n 3 + 11n = 12 + 2n Solving 3 + 11n = 12 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 3 + 11n + -2n = 12 + 2n + -2n Combine like terms: 11n + -2n = 9n 3 + 9n = 12 + 2n + -2n Combine like terms: 2n + -2n = 0 3 + 9n = 12 + 0 3 + 9n = 12 Add '-3' to each side of the equation. 3 + -3 + 9n = 12 + -3 Combine like terms: 3 + -3 = 0 0 + 9n = 12 + -3 9n = 12 + -3 Combine like terms: 12 + -3 = 9 9n = 9 Divide each side by '9'. n = 1 Simplifying n = 1
| x-12=2x | | 9x+19x=112 | | 3(x-4)=5x-36 | | 3t=-45 | | 6y=-30 | | -9(3b+3)+(28b-1)=0 | | 3.9q-5.5-4.4q=-1.5q-1.9 | | 876x+65=87 | | 13x+7-3=12x-4 | | x+12+x-15= | | 6x-15=57 | | -15y=105 | | R+(-12)=3 | | X-37=75 | | 0.5*20+0.6*20+8=20 | | -3b+7=9b+11 | | 0.5*20+0.6*20+8= | | x^2+4-48=1 | | 1.3x-0.7(x-6)=0.6(x-7) | | 35=8c-3 | | 0.8p+2=0.4(p+8)+0.4(p+1) | | 7a-4=6a+9 | | 6x-9x-7=-3x+3-7 | | 3x+4=3x+4 | | 2g-3=19 | | 2(x+1)-6=4x-2(1+x) | | 6x-3=4(x+1)+2x-7 | | -2(t-4)+5t=6t-2 | | 2(x-4)+3=3(x+1)+1 | | 6(5x-9)+3=30x-51 | | 3x+5=3(x+7) | | -3y+9=-3(2y+1) |